(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In today’s globalized world, learning English as a second language (ESL) has become crucial since it offers chances for social, professional, and academic advancement. Through an analysis of several learning methodologies, such as immersion, shadowing, flashcards, and interactive exercises, this study investigates efficient ways to improve English competence. The most effective strategies are highlighted by combining theoretical analysis with empirical data collected through surveys and observations. The findings show that active participation and immersive experiences greatly improve language learning. However, efficacy is influenced by individual characteristics, including age and learning style. The study ends with suggestions for teachers and students to maximize ESL instruction.